Do Participatory Leadership Style, Motivation, and Work Environment Affect Employee Performance? Lessons from Local Organization in An Emerging Country - Endah Suryani; Ferdinandus Christian; Mohammad Imam Farisi (Britain International for Academic Research (BIAR) Publisher, 2021)
This study aims to determine the effect of participatory leadership style, motivation and work environment on employee performance at the Department of Public Works and Public Housing (PUPR) of Yapen Islands Regency, Papua, Indonesia. This research is a quantitative research with the sources of data collected in this study are primary data and secondary data. This study used a saturated sample with a total of 101 people and applied multiple regression to analyse the data. It found that the participatory leadership did not affect the employee performance, while motivation and work environment influence the employee performance. It implies that the latter variables are the employee performance’s key drivers and should be the main priorities.